Clinical Applications and Future Directions of Functional MRI - Orringer, Daniel A.; Vago, David R.; Golby, Alexandra J. (Seminars in Neurology, 2012)
First described for use in mapping the human visual cortex in 1991, functional magnetic resonance imaging (fMRI) is based on blood-oxygen level dependent (BOLD) changes in cortical regions that occur during specific tasks. Typically, an overabundance of oxygenated (arterial) blood is supplied during activation of brain areas. Consequently, the venous outflow from the activated areas contains a higher concentration of oxyhemoglobin, which changes the paramagnetic properties of the tissue that can be detected during a T2-star acquisition. fMRI data can be acquired in response to specific tasks or in the resting state. fMRI has been widely applied to studying physiologic and pathophysiologic diseases of the brain. This review will discuss the most common current clinical applications of fMRI as well as emerging directions.
Keywords: functional magnetic resonance imaging (fMRI); blood oxygenation level dependent (BOLD); tractography; tumor mapping; language lateralization; traumatic brain injury (TBI); epilepsy surgery